Parkbuddy – Find My Car Android Mobile Application - Francis, Flora Stephanie; Jali, Nurfauza; Fauzi, Ahmad Hadinata; Jali, Suriati Khartini (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
As a result of technological progress, smartphones become an excellent choice for the user to make their life easier. This paper discussed how to locate parked vehicle using mobile application. The situation of forgetting where last vehicle location was parked and trying to remember it can become problem to some people especially to those who are having deterioration of memory such as a short term memory and dementia. This mobile application helps these users to locate their vehicle by utilising the global positioning system (GPS) system. This paper presents and critically analyses the system developed to solve the problem.